PEMBUKUAN DAN OPTIMALISASI WHATSAPP BUSINESS DALAM MENINGKATKAN PENJUALAN HOME INDUSTRI - Heni Risnawati; Nur Hayati; Hafni Aulida (Universitas Muhammadiyah Kudus, 2024)
There is various information that can be distributed, such as educational material to increase knowledge about bookkeeping and optimizing WhatsApp to increase sales for home industry businesses. In home industry businesses, it is very important to optimize the WhatsApp Business application as a promotional tool to increase sales. Apart from that, bookkeeping or recording financial reports is also very important. Systematic bookkeeping is useful in providing reliable cash information regarding a business's financial position at a certain time. The aim of this activity is to provide additional knowledge to the community, especially those in Klaling Village, Kudus Regency, about simple bookkeeping methods and optimizing WhatsApp Business. The method used in this activity is lecture and participatory discussion. The results obtained by the participants were that participants were able to make simple bookkeeping and were able to optimize the use of WhatsApp Business to increase sales in home industry businesses.Keywords: Bookkeeping, Optimization, WhatsApp Business, Home Industry